Violent crime, hate speech or terrorism? How Canada views and prosecutes far-right extremism (2001–2019). (March 2021) - Nesbitt, Michael
Fifty-six individuals were charged with terrorism between December 2001 when Canada first enacted its antiterrorism criminal offences and December 2019. Not a single such individual was associated with a far-right group or espoused a far-right ideology. Over the same period of time, Canada saw a rise in far-right violence and crime, including several deadly attacks that raised the spectre of terrorism. This article seeks to identify why terrorism has not been associated with the activities of those on the far right, how Canada has prosecuted far-right violence if not for terrorism and what the implications are for Canada's criminal prosecutions going forward. It finds that since December 2001 all publicly reported hate speech cases and cases where an individual's sentence was aggravated for hate have involved individuals espousing far-right rhetoric; likewise, all but one case where the media raised the spectre of terrorism but no such charge ensued can be described as being motivated by far-right ideation. In the result, Canadian law punishes more seriously Al-Qaida (AQ)-inspired extremism than far-right extremism, while stigmatizing the former more than the latter. The time has thus come to tackle head-on the concept of ideology in Canadian criminal law, and how the law treats various ideologies.